The impact of investors' knowledge, profit and benefit towards the investors' acceptance on new mathematical formulation of Islamic unit trust model - Siti Nadhirah Mohamad Fauzi
One of the main differences between Islamic and conventional unit trust is Islamic unit trust funds must follow the Shariah guidelines. Therefore, there are two processes that they are need to undergo which are screening process and purification process. The screening process is under responsibility of Shariah Advisory Council (SAC) of the Securities Commission (SC). However, the purification process in Malaysia is under responsibility of investors themselves. The final profit distribution does not include the payment of zakat. Hence, to fill in the gap discovered where the final profit distribution does not include the payment of zakat, this study proposes a new mathematical formulation ofIslamic unit trust model which include the payment zakat for purification process and additional benefit in Takaful for investors. The first objective of this study is to compare the existing various unit trust models in Malaysia. The second objective is to construct a new mathematical formulation of Islamic unit trust models. The third objective is to examine the acceptance of the new mathematical formulation ofIslamic unit trust model among investors. Firstly, a comparison of information needed from various unit trust product brochures and official websites is made and studied. Then, a new mathematical formulation of Islamic unit trust model is constructed. This new formula constructed based on the existing formulation of the unit trusts which are a simple interest and the gaps discovered are the payment of zakat/tax and benefit for investors. A total of200 questionnaires were distributed among unit trust holders whom are having at least one unit of any unit trust fund in Malaysia to examine the investors' acceptance on the new mathematical formulation ofIslamic unit trust model. This study was done in eight districts of Terengganu which are Kuala Terengganu, Kuala Nerus, Setiu, Besut, Marang, Hulu Terengganu, Dungun and Kemaman. Structural Equation Modelling (SEM) was used in order to test the hypothesis of this study by using Statistical Package for Social Science (SPSS) AMOS software. Research analysis showed that the independent variables which are investors' knowledge, profits and benefits had a significant direct effect towards dependent variable which is investors' acceptance on new mathematical formulation of Islamic unit trust model. The regression weight for investors' acceptance towards investors' knowledge is 0.235 (p value < 0.05), which means that there is a significant effect of investors' acceptance towards investors' knowledge. The regression weight for investors' acceptance towards investors' profit is 0.127 (p-value < 0.05) which means that there is a significant effect of investors' acceptance towards investors' profit. The regression weight for investors' acceptance towards investors' benefit is 0.522 (p-value < 0.05) which means there is a significant effect of investors' acceptance towards investors' benefit. This conveys that the investors agreed with the new mathematical formulation ofIslamic unit trust model which provides additional benefit for the investors while fo llowing the Shariah guidelines. Thus, they accepted the new mathematical formulation ofIslamic unit trust model to be available in the unit trust market. In conclusion, this study provides a new mathematical formulation for Islamic unit trust which includes the payment for zakat and additional benefit in Takaful for investors. Hence, the investors can gain purified final profit distribution with additional benefit in Takaful.